2017
DOI: 10.1175/jcli-d-16-0552.1
|View full text |Cite
|
Sign up to set email alerts
|

Greenland Clouds Observed in CALIPSO-GOCCP: Comparison with Ground-Based Summit Observations

Abstract: Spaceborne lidar observations from the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observations ( CALIPSO) satellite provide the first-ever observations of cloud vertical structure and phase over the entire Greenland Ice Sheet. This study leverages CALIPSO observations over Greenland to pursue two investigations. First, the GCM-Oriented CALIPSO Cloud Product ( CALIPSO-GOCCP) observations are compared with collocated ground-based radar and lidar observations at Summit, Greenland. The liquid cloud cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…The seasonal trend at Barrow, which is adjacent to the ocean and only covered by scattered snow in summer, is similar to that in the southern ablation zone of the GrIS. The seasonal cycle in the northern accumulation zone on the GrIS agrees with cloud fraction and liquid water content variabilities at Summit reported in Miller et al (), cloud fraction in northern and central Greenland reported in Starkweather (), and liquid cloud fraction in northern Greenland reported in Lacour et al (). On the rest of the GrIS, longwave CRE responds to clouds in an almost opposite manner to shortwave ↓ CRE throughout the season (Figure d).…”
Section: Cre Seasonal Variabilitysupporting
confidence: 87%
See 2 more Smart Citations
“…The seasonal trend at Barrow, which is adjacent to the ocean and only covered by scattered snow in summer, is similar to that in the southern ablation zone of the GrIS. The seasonal cycle in the northern accumulation zone on the GrIS agrees with cloud fraction and liquid water content variabilities at Summit reported in Miller et al (), cloud fraction in northern and central Greenland reported in Starkweather (), and liquid cloud fraction in northern Greenland reported in Lacour et al (). On the rest of the GrIS, longwave CRE responds to clouds in an almost opposite manner to shortwave ↓ CRE throughout the season (Figure d).…”
Section: Cre Seasonal Variabilitysupporting
confidence: 87%
“…Cloud fraction from the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) also increases throughout the melt season in the north. However, it slightly decreases from May to June in the south (Lacour et al, ). Liquid‐containing clouds, which contribute more to surface melt than ice‐only clouds (Bennartz et al, ; Kay et al, ; Miller et al, ), increase continually in both northern and southern Greenland during the melt season, with a larger variability in the north (Lacour et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cesana et al (2015) and Liu and Key (2016) use cloud retrievals from active sensors to evaluate reanalyses and model simulations. However, active sensor retrievals can only be cross-validated at Summit, the sole station with comprehensive cloud measurements inside Greenland (Lacour et al, 2017;Shupe, Turner, et al, 2013).…”
Section: Supporting Informationmentioning
confidence: 99%
“…Shortwave cooling by clouds is weakest near Summit due to the constantly high albedo. Longwave warming is strongest there probably due to the dry atmosphere and prevalent low-level liquid-containing clouds (Lacour et al, 2017;Miller et al, 2015;Shupe, Turner, et al, 2013). These clouds most likely form by orographic lifting during warm southerly advection (Zygmuntowska et al, 2012) and are usually decoupled from the surface (Curry et al, 1996;Shupe, Persson, et al, 2013;Tjernström et al, 2014) as the boundary layer is drier at higher elevations.…”
Section: Cre Spatial Distribution From In Situ Measurementsmentioning
confidence: 99%